Aprosdokitos mikrotero gen. et sp. nov., the tiniest Sphenisciformes that lived in Antarctica during the Paleogene - Acosta Hospitaleche, Carolina Ileana Alicia (2017)
A small humerus from Eocene levels of Seymour Island, Antarctica is assigned here to Aprosdokitos mikrotero sp. and gen. nov. (Aves, Sphenisciformes), based predominantly on its small size. An ontogenetic series based on Pygoscelis antartica was established for comparative purposes, and evaluation of pathological conditions was also carried out in order to rule out other possible sources of size variation.